The slow demise of Easter Island: insights from a modeling investigation - Brandt, Gunnar; Merico, Agostino (Frontiers in Ecology and Evolution, 2015)
The history of Easter Island and its supposed social-ecological collapse is often taken as a grim warning for the modern world. However, while the loss of a once lush palm forest is largely uncontested, causes and timing of the collapse remain controversial, because many paleoeological and archaeological data are afflicted with considerable uncertainties. According to a scenario named ecocide, the overharvesting of palm trees triggered a dramatic population decline, whereas a contrasting view termed genocide deems diseases and enslavement introduced by Europeans as the main reasons for the collapse. We propose here a third possibility, a slow demise, in which aspects of both ecocide and genocide concur to produce a long and slow decline of the society. We use a dynamic model to illustrate the consequences of the three alternatives with respect to the fate of the paleoecological system of the island. While none of the three model scenarios can be safely ruled out given the uncertainties of the available data, the slow demise appears to be the most plausible model scenario, in particular when considering the temporal pattern of deforestation as inferred from radiocarbon dates of charcoal remains.